2003
DOI: 10.1104/pp.103.027094
|View full text |Cite
|
Sign up to set email alerts
|

A Developmental Response to Pathogen Infection in Arabidopsis

Abstract: We present evidence that susceptible Arabidopsis plants accelerate their reproductive development and alter their shoot architecture in response to three different pathogen species. We infected 2-week-old Arabidopsis seedlings with two bacterial pathogens, Pseudomonas syringae and Xanthomonas campestris, and an oomycete, Peronospora parasitica. Infection with each of the three pathogens reduced time to flowering and the number of aerial branches on the primary inflorescence. In the absence of competition, P. s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
86
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(92 citation statements)
references
References 59 publications
5
86
1
Order By: Relevance
“…The direction and magnitude of selection on rosette size and flowering time is similar to what has been reported in other studies (reviewed in Pigliucci, 2003). Selection for less bacterial growth is not surprising considering that infection by P. syringae has been shown to reduce fitness in A. thaliana in other studies (Kover and Schaal, 2002;Korves and Bergelson, 2003). However, the positive relationship between symptom severity and fitness is very surprising.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The direction and magnitude of selection on rosette size and flowering time is similar to what has been reported in other studies (reviewed in Pigliucci, 2003). Selection for less bacterial growth is not surprising considering that infection by P. syringae has been shown to reduce fitness in A. thaliana in other studies (Kover and Schaal, 2002;Korves and Bergelson, 2003). However, the positive relationship between symptom severity and fitness is very surprising.…”
Section: Discussionsupporting
confidence: 62%
“…As with any other selection study, the observed patterns of selection are dependent on the environmental conditions experienced by the plants in the growth chamber and only reflect plant response to infection at a specific developmental stage. Although no phenotypic correlation was observed between either rosette size or flowering time and the two susceptibility-related traits in our study, other studies have shown that infected plants tend to flower earlier than uninfected plants (Peters, 1999;Korves and Bergelson, 2003). Since we found that selection favors earlier flowering in infected plants, it is possible that selection on tolerance-related traits (ie traits that alter the effect of infection on fitness) are more important than resistance-related traits (ie traits that affect the degree to which plants become infected).…”
Section: Discussioncontrasting
confidence: 47%
“…Hyaloperonospora arabidopsidis (Hpa)-infected plants show curving of the leaves (Fig. 1) and early flowering (Korves and Bergelson 2003). Interestingly, in response to different plant pathogens, a similar developmental phenotype can be observed.…”
mentioning
confidence: 64%
“…Plant parasitic nematodes as well as Xanthomonas provoke plant cell hyperplasia and hypertrophy (Caillaud et al 2008;Kay and Bonas 2009). In response to Pst, Xanthomonas, and Hpa, plants reduce time to flower and the number of aerial branches on the primary inflorescence (Korves and Bergelson 2003). These changes are prevented in a resistant plant, such as one carrying RPS2 (Korves and Bergelson 2003).…”
mentioning
confidence: 99%
See 1 more Smart Citation